2002
DOI: 10.1046/j.1528-1157.43.s.5.3.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Treatment Protects GABAB Inhibition in the Dentate Gyrus of Female Rats after Kainic Acid–Induced Status Epilepticus

Abstract: Summary: Purpose:We used the paired-pulse inhibition paradigm to determine whether the cell loss in the hilus of the dentate gyrus of female rats after kainic acid (KA)-induced status epilepticus (SE) is associated with functional changes in the dentate gyrus. Additionally, we determined whether the lost function could be preserved by using estrogen neuroprotection.Methods: Female rats were ovariectomized and treated either with estrogen replacement (four doses of 2 g of estradiol every 24 h: two doses before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
(23 reference statements)
2
19
0
Order By: Relevance
“…Horizontal slices (4ϫ oil, n ϭ 22; 4ϫ ␤-estradiol, n ϭ 22; 1ϫ oil, n ϭ 18; 1ϫ ␤-estradiol, n ϭ 8) containing the dorsal hippocampus (400 m thick) were cut on a vibratome in ice-cold artificial CSF (ACSF) (in mM: 126 NaCl, 5 KCl, 1.25 NaH 2 PO 4 , 2 MgCl 2 , 2 CaCl 2 , 26 NaHCO 3 , and 10 glucose, pH 7.36). The slices were preincubated in an interface chamber in warmed (34 -35°C) and oxygenated ACSF (5% CO 2 /95% O 2 ) for at least 1 h. Paired square pulses (50 -400 A, 150 s duration) were delivered via a stainless steel bipolar stimulating electrode (Frederick Haer Company, Bowdoinham, ME) positioned over the outer and middle third of the molecular layer (mixed perforant path stimulation) (Velíšek and Velíšková, 2002) using a stimulator coupled to a stimulus isolation unit (A.M.P.I., Jerusalem, Israel). Interstimulus intervals between the paired stimuli ranged from 10 to 1000 ms, corresponding to frequencies of 100 to 1 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Horizontal slices (4ϫ oil, n ϭ 22; 4ϫ ␤-estradiol, n ϭ 22; 1ϫ oil, n ϭ 18; 1ϫ ␤-estradiol, n ϭ 8) containing the dorsal hippocampus (400 m thick) were cut on a vibratome in ice-cold artificial CSF (ACSF) (in mM: 126 NaCl, 5 KCl, 1.25 NaH 2 PO 4 , 2 MgCl 2 , 2 CaCl 2 , 26 NaHCO 3 , and 10 glucose, pH 7.36). The slices were preincubated in an interface chamber in warmed (34 -35°C) and oxygenated ACSF (5% CO 2 /95% O 2 ) for at least 1 h. Paired square pulses (50 -400 A, 150 s duration) were delivered via a stainless steel bipolar stimulating electrode (Frederick Haer Company, Bowdoinham, ME) positioned over the outer and middle third of the molecular layer (mixed perforant path stimulation) (Velíšek and Velíšková, 2002) using a stimulator coupled to a stimulus isolation unit (A.M.P.I., Jerusalem, Israel). Interstimulus intervals between the paired stimuli ranged from 10 to 1000 ms, corresponding to frequencies of 100 to 1 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the role of Y 1 , Y 2 , and Y 5 NPY receptors, the following specific antagonists to individual NPY receptors were bath applied for at least 30 min before recording: 100 (El Bahh et al, 2002;Tu et al, 2005) (Y 2 receptor antagonist; 30 nM, n ϭ 8; 100 nM, n ϭ 6), and 250 nM 5,5-dimethyl-2-(2,3,4,9-tetrahydro-3,3-dimethyl-1 oxo-1H-xanthen-9-yl)-1,3-cyclohexanedione (L-152,804) (Woldbye et al, 2005) (Y 5 receptor antagonist; n ϭ 5). To determine the role of GABA B receptors in the ␤-estradiol-induced enhancement of the late paired-pulse inhibition, 400 M (3-aminopropyl)(diethoxymethyl)phosphinic acid (CGP 35348) (Velíšek and Velíšková, 2002) was bath applied for at least 30 min before recordings (n ϭ 10). LY 341495 [(2S)-2-amino-2-[(1S,2S)-2-carboxycycloprop-1-yl]-3-(xanth-9-yl) propanoic acid] was bath applied for at least 30 min before recordings at 20 M (n ϭ 8) or 200 nM (n ϭ 7) to determine the role of metabotropic glutamate receptors (mGluRs) in the effects of ␤-estradiol pretreatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Baclofen has long been known to have antinociceptive activity in acute and chronic pain models (Hwang and Yaksh, 1997). On the other hand, pretreatment with estrogen can save GABA B receptor function, probably by neuroprotection of neurons containing postsynaptic GABA B receptors (Velisek and Veliskova, 2002). Noriega et al (2010) reported that estrogen decreases the functional coupling of the mu-opioid and GABA B receptors to the inwardly rectifying K + channel, possibly through an action on the G-protein (Noriega et al, 2010).…”
Section: Introductionmentioning
confidence: 99%